Changing inter-molecular spin-orbital coupling for generating magnetic field effects in phosphorescent organic semiconductors - Yan, Liang; Shao, Ming; Graeff, Carlos Frederico de Oliveira [UNESP]; Hummelgen, Ivo; Ma, Dongge; Hu, Bin (American Institute of Physics (AIP), 2012)
Phosphorescent organic semiconductors normally show negligible magnetic field effects in electronic and optic responses. These phenomena have been generally attributed to strong spin-orbital coupling which can dominate internal spin-dephasing process as compared with applied magnetic field. This paper reports both positive and negative magnetocurrents from phosphorescent organic semiconductors through dissociation and charge-reaction channels when the intermolecular spin-orbital coupling is changed based on materials mixing. Our experimental results indicate that inter-molecular spin-orbital coupling is essentially responsible for the generation of magnetic field effects in phosphorescent organic semiconductors. (C) 2012 American Institute of Physics. [doi:10.1063/1.3673561]